Manajemen Pengenalan Agama Islam Melalui Penanaman Nilai pada Anak Usia Dini di Raudhatul Athfal - Nurhasanah R; Mira Humaira (Institusi Agama Islam Negeri (IAIN) Bone, 2021)
This study discusses the instilling of Islamic Religious Education Values in Early Childhood in Raudhatul Athfal (RA) Nurul Aeyn As Adiyah Kampung Baru, Bone Regency. The aims of this study were (1) to describe the form of inculcating Islamic Religious Education values in early childhood in Raudhatul Athfal (RA) Nurul Aeyn As Adiyah Kampung Baru, Bone Regency, (2) to find out the supporting and inhibiting factors in the process of inculcating the values of Religious Education. Islam in early childhood in Raudhatul Athfal (RA) Nurul Aeyn As Adiyah Kampung Baru, Bone Regency, (3) knowing the solution to the inhibiting factors in the process of instilling Islamic Religious Education values in early childhood in Raudhatul Athfal (RA) Nurul Aeyn As Adiyah Kampung Baru, Bone Regency. To obtain data in the study, researchers used qualitative research methods, with descriptive analysis. Data collection techniques used in this study were observation, interviews, and documentation. Based on the results of the research carried out, it was concluded that the form of instilling the values of Islamic Religious Education in early childhood in Raudhatul Athfal (RA) Nurul Aeyn As Adiyah Kampung Baru, Bone Regency was carried out through planting Islamic religious education taught at any time through habituation activities, saying the word -polite words both to friends and teachers and to older people, say thank you if something is given, and say sorry if you make a mistake. Supporting factors in inculcating the values of Islamic religious education in early childhood, among others: a) educators are experts and professionals, have taken PAUD teacher education and animate their profession, educators attend workshops, training, upgrading and routine coaching from foundations, b ) facilities and infrastructure that are adequate and support learning, c) the availability of learning media both traditional, simple, and modern, d) the condition of children who are enthusiastic and ready to learn. In instilling the values of Islamic religious education in early childhood also encountered several obstacles, including: a) different family backgrounds and environments. b) the potential, motivation, interests, problems, conditions, characters, and attitudes of each child are different, c) there are children who are active and difficult to be conditioned, d) students who are still difficult to focus on the learning provided teachers, e) the condition of parents who do not all provide further education to guide and habituate children at home.